Barriers and enablers in the implementation of a program to reduce cesarean deliveries - Clara Bermúdez-Tamayo; Emilia Fernández Ruiz; Guadalupe Pastor Moreno; Gracia Maroto-Navarro; Leticia Garcia-Mochon; Francisco Jose Perez-Ramos; Africa Caño-Aguilar; Maria del Pilar Velez (BMC, 2017)
Abstract Background Conducting audits, implementing best practices and giving feedback to the professionals have shown considerable promise in reducing rates of cesarean delivery and mother-child morbidity. The purpose of the study is two-fold: a) to identify the factors that facilitate change in current practices and thus reduce the use of obstetric interventions, and b) to better understand the barriers to such changes. To reach these objectives, the study analyzed the experiences of professionals participating in a program to reduce cesarean rates in 20 hospitals in Andalusia (Spain). Methods A qualitative exploratory study was conducted. Participants were 14 ob-gyns and 14 nurse-midwives who work for Spain's National Healthcare System and have been involved in the program. To gather information, in-depth individual interviews were used. The interview was designed to examine factors affecting the quality of care, such as issues related to policy/management, hospitals, practitioners and patients. Results The barriers identified include: 1) At the policy/management level: limited influence of institutional policy and the scant political commitment perceived. 2) At the organizational level: separation of the hierarchical structure of doctors from that of nurse-midwives, few positive incentives and the strong threat of sanctions for malpractice, inappropriate reorganization of midwife/obgyns competences. 3) At the healthcare staff and facility level: reluctance to change accentuated by years of professional practice. 4) Physical resources: obsolete delivery rooms with a medical look. 5) At the professional level: medical and legal pressure, cesarean delivery considered safe in the event of a legal claim, low motivation due to decline in working conditions, convenience-based practices. 6) Woman giving birth and her family: fear of pain, impatience while waiting for process to occur, misinformation. The enablers include: 1) At the organizational level: good coordination with pediatrics and emergency departments, 2) Training: skills updates for a less-interventionist approach, increased awareness, 3) Health professionals: satisfaction for a job well done, recognition by patients. 4) Woman giving birth: information circuits for patients and their families, trust in health professionals. Conclusions The results can contribute to the design of more effective knowledge translation interventions to reduce cesarean sections, based on overcoming obstacles, reinforcing enabling factors and attempting to (re)define the boundaries between research and practice.